Mental health problems among inhabitants of old age homes: A preliminary study - Tiwari, S. C. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: An exceptional increase in the number and proportion of older adults in the country, rapid increase in nuclear families, and contemporary changes in psychosocial matrix and values often compel this segment of society to live alone or in old age homes. As this group of people is more vulnerable to mental health problems, therefore a pilot study was carried out by the Department of Geriatric Mental Health, Lucknow with following aim. AIM: To study mental health and associated morbidities among inhabitants of old age homes. MATERIALS AND METHODS: It was an exploratory study in which information about available old age homes at Lucknow were obtained and three of them were randomly selected. All the heads of these institutions were contacted and permission to carry out the study was obtained. Consent from the participants was obtained. Survey Psychiatric Assessment Schedule (SPAS), Mini Mental State Examination (MMSE), Mood Disorder Questionnaire (MDQ), and SCAN-based clinical interviews were applied for assessment by a trained research staff. RESULTS: Forty five elderly inhabitants who had given their consent to participate in the study were interviewed. Depression (37.7%) was found to be the most common mental health problem followed by anxiety disorders (13.3%) and dementia (11.1%). CONCLUSIONS: A majority of the inhabitants (64.4%) were having psychiatric morbidity and no one was observed physically fit. Large sample studies are needed to substantiate the observations.